Financial crises, payment system risk and oversight - O'Connor, Sean (Henry Stewart Talks, 2010)
Central role of payment and settlement systems in the financial system and the organization of payment and settlement systems and service arrangements, Financial crises and payment and settlement risk, Financial market behavior, activity and related risks, Features of the recent financial crisis and impact on payment and settlement systems, Role of payment system oversight in financial system policy and the activities of payment system oversight during and after financial crises, Lessons learned for payment system policy and oversight, Issues and policy proposals regarding infrastructure, risk measurement and controls, availability of settlement funds, and the oversight framework